Textual Discourse Analysis in the Raya and the Last Dragon Movie - Ni Luh Gede Retno Savitri; I Gusti Ayu Vina Widiadnya Putri (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
is study examines textual discourse in the animated movie “Raya and the Last Dragon,” with a focus on grammatical and lexical cohesion to understand how language supports narrative coherence and emotional impact. Although there is substantial research on textual cohesion and discourse patterns in various contexts, there is a notable gap in investigating how animated films, which merge visual and verbal elements, use these linguistic techniques to construct complex narratives. This research addresses this gap by applying Halliday and Hasan's (1976) theoretical framework to analyze how cohesive devices function within the film’s dialogues. Through the descriptive-qualitative method, the research explores cohesive devices to enhance our comprehension of this linguistic phenomenon. Data collection involved meticulously observing the movie and analyzing the data through both formal and informal methods. The analysis revealed 416 instances of grammatical elements, with references being the most frequently used. These references ensure clarity and continuity in dialogues by linking back to previously mentioned characters or objects, thereby keeping the conversation smooth and coherent. In the lexical analysis, 78 instances were identified, with repetition being the most common. Repetition emphasized key themes, strengthened emotional connections, and effectively conveyed the movie's main messages. This study provides new insights into how animated films uniquely employ cohesive devices to enhance storytelling and character development, and contributing to the broader field of textual discourse analysis.